Adrenergic signals influence proteomic responses in breast cancer cells - Carrasco, Manuel; Bjørnstad, Ole Vidhammer; Vethe, Heidrun; Akslen, Lars A. (Frontiers in Neuroscience, 2025)
IntroductionBreast cancer remains a major health challenge due to its molecular heterogeneity and complex interactions with the tumor microenvironment. Adrenergic signaling, mediated by stress hormones such as noradrenaline, has emerged as a potential regulator of cancer progression, influencing cell proliferation, cell adhesion, migration, and invasion.MethodsThis study investigates the effects of adrenergic modulation on breast cancer spheroids from basal-like (MDA-MB-231, BT549) and luminal-like (T47D, MCF7) cell lines, using 3D culture systems as a more physiologically relevant model compared to traditional 2D monolayer cultures. The 3D spheroid model better recapitulates the structural complexity of tumors, providing insights into cell–cell and cell-matrix interactions that influence signaling pathways and drug responses.ResultsNoradrenaline treatment significantly reduced spheroid size, invasion capacity, and the expression of EMT-related markers and integrins in MDA-MB-231 cells. These effects were partially reversed by propranolol, a non-selective beta-adrenergic receptor antagonist. Luminal-like spheroids, characterized by low ADRB2 abundance, displayed limited responsiveness to adrenergic modulation. Proteomic analysis revealed distinct subtype-specific responses, with basal-like spheroids showing pronounced alterations in pathways related to proliferation, cytoskeletal dynamics, epithelial-mesenchymal transition, and metabolism, whereas luminal-like spheroids exhibited minimal changes.DiscussionOur findings reveal heterogeneity in adrenergic receptor signaling across basal-like and luminal-like breast cancer cell lines, and also within the basal-like subgroup. This diversity underscores the complexity of adrenergic signaling in breast cancer and highlights the advantages of 3D culture systems. These results provide valuable insights into the subtype-specific patterns of response to adrenergic signaling that contribute to tumor progression and may inform future studies including evaluation of therapeutic strategies.